The Management of Elbow Instability Using an Internal Joint Stabilizer: Preliminary Results - Orbay, Jorge L. (Springer US, 2014)
BACKGROUND: Nonsurgical and surgical treatments such as immobilization, transarticular pinning, and hinged or nonhinged external fixation have been used to treat unstable elbows. These methods all have drawbacks. We thought that a bent Steinmann pin introduced through the axis of ulnohumeral rotation and attached to the ulna could provide an improved method of treatment and that this could result in the development of a proper internal joint fixator that may have widespread application. QUESTIONS/PURPOSES: Does a fully internal hinged fixator crafted intraoperatively by the surgeon from a Steinmann pin for patients undergoing surgery for severe elbow instability result in restoration of range of motion and elbow stability? Does it result in new complications? METHODS: We reviewed the first 10 patients treated with the method for elbow instability. Diagnoses included fracture-dislocations of the elbow that remain unstable after fracture repair and unstable elbows that result from release of contracture or ulnohumeral synostosis. During that time, all patients meeting these criteria who underwent surgery by this surgeon (JLO) were treated with this approach. Charts, radiographs, and therapy notes were assessed at a minimum of 14 months (mean, 32 months; range, 14–59 months); no patients were lost to followup. Data recorded included age, sex, and elbow and forearm range of motion as well as any complications and reoperations that occurred. The absence of elbow instability was determined initially by radiographically observing concentric reduction of the ulnohumeral and radiocapitellar joints and later by radiography plus the absence of clinical signs and symptoms of elbow instability. RESULTS: Mean range of motion at latest followup was flexion 134°, extension −19°, pronation 75°, and supination 64°. All elbows were clinically and radiographically stable. Complications resulting in additional procedures occurred in four patients, including one recurrent deep infection in a patient with a remote history of sepsis, one wound hematoma that resolved after a drainage procedure performed in the office, one prominent implant treated by partial removal, and one patient with heterotopic ossification treated with excision of the heterotopic bone. CONCLUSIONS: This technique restores elbow stability and permits motion without the use of transcutaneous pins. It seems promising for the treatment of patients with severe elbow instability but requires a second procedure for removal. Further investigation is needed to understand its place in the surgeon’s toolbox and what drawbacks it may have. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.